Peran Majelis Taklim al-Hidayah sebagai Penyelenggara Kegiatan Keagamaan untuk Warga Negara Indonesia di Kota Riyadh - Irsyad Rafi; Anugrah Anugrah (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
This Community Service Program (PkM) aims to increase the religious understanding of Indonesian citizens in the city of Riyadh through the role of the Al-Hidayah Taklim Council. The PkM method used is the implementation of Al-Hidayah taklim assemblies, such as al-Qur'an halaqah with two main activities, namely tahsin and tahfiz, Arabic halaqah, scientific studies, including fiqh, aqidah, Al-Qur'an sciences. and studies with special themes according to certain moments. This activity program is carried out regularly on Fridays and Saturdays flexibly. The result of this PkM is that apart from being a place of learning that is able to increase religious knowledge for Indonesian citizens, the taklim assembly also acts as a forum that strengthens and strengthens friendship and social relations between Indonesian citizens, instilling the values ​​of solidarity and brotherhood, as well as moral and spiritual values. The taklim assembly also has an important role in assisting the Embassy of the Republic of Indonesia (KBRI) in providing protection and shelter for Indonesian citizens in the city of Riyadh. The taklim assembly as a social and educational institution plays an active role in collaborating with the Indonesian Embassy in ensuring the welfare and needs of Indonesian citizens, especially in religious aspects. The existence of the Al-Hidayah Taklim Council and its role has had a positive impact on Indonesian citizens in the city of Riyadh.